Purification and Characterization of Two Highly Thermophilic Alkaline Lipases from Thermosyntropha lipolytica - Salameh, Moh'd A. (American Society for Microbiology (ASM), 2007)
Two thermostable lipases were isolated and characterized from Thermosyntropha lipolytica DSM 11003, an anaerobic, thermophilic, alkali-tolerant bacterium which grows syntrophically with methanogens on lipids such as olive oil, utilizing only the liberated fatty acid moieties but not the glycerol. Lipases LipA and LipB were purified from culture supernatants to gel electrophoretic homogeneity by ammonium sulfate precipitation and hydrophobic interaction column chromatography. The apparent molecular masses of LipA and LipB determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis were 50 and 57 kDa, respectively. The temperature for maximal activity of LipA and LipB was around 96°C, which is, so far as is known, the highest temperature for maximal activity among lipases, and the pH optima for growth determined at 25°C (pH(25°C) optima) were 9.4 and 9.6, respectively. LipA and LipB at 100°C and pH(25°C) 8.0 retained 50% activity after 6 and 2 h of incubation, respectively. Both enzymes exhibited high activity with long-chain fatty acid glycerides, yielding maximum activity with trioleate (C(18:1)) and, among the p-nitrophenyl esters, with p-nitrophenyl laurate. Hydrolysis of glycerol ester bonds occurred at positions 1 and 3. The activities of both lipases were totally inhibited by 10 mM phenylmethylsulfonyl fluoride and 10 mM EDTA. Metal analysis indicated that both LipA and LipB contain 1 Ca(2+) and one Mn(2+) ion per monomeric enzyme unit. The addition of 1 mM MnCl(2) to dialyzed enzyme preparations enhanced the activities at 96°C of both LipA and LipB by threefold and increased the durations of their thermal stability at 60°C and 75°C, respectively, by 4 h.